The Effects of Using Interactive Multimedia to Increase Students’ Vocabulary at VIII Grade of SMPN 2 Jambi City in Academic Year 2019 - Atikah Mar’atunshalihah; Suyadi Suyadi (Universitas Batanghari Jambi, 2019)
This research was aimed to find out the effects of using interactive multimedia at the eighth grade students of SMPN 2 Jambi City in the academic year of 2019. The subject research was class VIIIB and VIIID. The instrument used in this thesis was test. In collecting the data, the researcher used pre-test. Before conducting post-test, the researcher gave treatment. After getting enough data, the researcher calculated the data using t-test. The result of this research was found the mean score of pre-test of Experiment class is 45.02 and the mean of post-test 80.48. To see whether the hypothesis is accepted or rejected, the significance value in the table above was .306, which means that the significance value is greater than 0.05, based on decision in the statistical correlation test, there is no relationship between pre-test and post-test. Paired sample t-test is used to determine whether there are difference can be seen from the sig value (2-tailed), the value in the table above is 0.000, so it can be concluded that the results of the effects of using Interactive Multimedia to increase students’ vocabulary are real significant on the pre-test and post-test data. Based on the result finding, it can be concluded that the data presented is there is an effects of using interactive multimedia towards students’ vocabulary mastery.